Telemetry System For Electronic Systems - Arslan, Coskun; Elaydin, Yunus Emre; Sails, Ziya Cem; Ayten, Umut Engin (IEEE, 2020)
The use, production and incentives provided by the state of electric and hybrid vehicles are increasing day by day. In this context the development of internal communication systems and control systems are increasing quickly. Smart control units are started to take the place of the mechanical parts that were used in the combustion engines. As result, process speeds are increased, reaction times are become shorter and more smart control units are started to develop. Beside the developed systems, the work done in order to decrease the process times improved the semiconductor sector. Increased processing speeds allow all units on the vehicle to be controlled by intelligent units, but also allow the monitoring of all these systems from a different center. As these systems continue to develop, autonomous vehicle systems that we see today and which we will encounter more frequently in the newfuture will ensure safe driving and become traceable. In this project a Val and a telemetry system that can controls and follow this system will he developed. VCU system is aiming that an internal safe and secure communication system by CAN Bus protocol with the aspects of isolation and immune to the EMI and other kind of interference. In the concern of system safety and testability VCU will be designed as two main sections. The sections to be designed as control unit and telemetry unit will be integrated into the vehicle by creating a modular structure. RF and GSM protocols will be placed on the telemetry unit and a flexible telemetry system with alternative will be installed.
Keywords: Engineering